Preliminary evaluation of reliability and validity of head and neck external lymphedema and fibrosis assessment criteria. (June 2016) - Deng, Jie; Dietrich, Mary S.; Ridner, Sheila H.; Fleischer, Arthur C.; Wells, Nancy; Murphy, Barbara A.
Abstract: Purpose: Measurement of head and neck external lymphedema and fibrosis (LEF) is challenging. To address this gap, we developed the Head and Neck External Lymphedema and Fibrosis (HN-LEF) Assessment Criteria. This article aimed to report preliminary data on reliability and validity of the HN-LEF Assessment Criteria. Methods: Sixty head and neck cancer (HNC) patients who were ≥3-month post cancer therapy were recruited. Study measures included 1) demographic/medical data; 2) LEF physical examination completed independently by two staff members for interrater reliability (intrarater reliability completed by one of them); and 3) grayscale ultrasound examination of the head and neck skin. Reliability estimates used percent agreement and Kappa statistic. Validity was assessed via Spearman correlations of physical examination findings with ultrasound measurements. Results: Fifty-one out of 60 HNC patients completed both physical examination and ultrasound assessments. Interrater reliability : 91.0% agreement (Kappa = 0.81, p  < 0.001) on the presence of types of LEF; 84.9% agreement regarding the grade of LEF (Kappa = 0.70, p  < 0.001) across all anatomic sites. Intrarater reliability: 96.1% agreement for type of LEF; and 91.4% agreement for grade across all sites. Ultrasound examination demonstrates characteristics and patterns for different types of LEF (particularly in the cheek, submental, and neck regions). Conclusions: The study provided initial reliability and validity data for a clinician-reported tool evaluating external LEF in the HNC population. These preliminary findings demonstrate that the tool had good reliability. Associations with the ultrasound examination results demonstrate that the tool validly captures soft tissue changes at select sites. Further validation of the tool is warranted. Highlights: The study shows initial reliability and validity of a tool evaluating external lymphedema and fibrosis in the HNC population. These preliminary findings demonstrate that the tool had good reliability. The ultrasound exam results show that the tool validly captures soft tissue changes in the cheek, submental, and neck regions. Further validation of the tool in larger and/or longitudinal studies is needed.